The Students’ Difficulties in Listening for Daily Context Course on the Second Semester of English Education Program - Amik Ludfatun Nuriah (Channing : Journal of English Language Education and Literature, 2021)
The purpose of this research is to understand the problems that students encounter when listening to the daily situational topics. The writer chose STKIP Nurul Huda's second semester English Education Program, with 34 students in the second semester. Collect data through questionnaire surveys, interviews and observations. The questionnaire was conducted from three aspects: listening materials, listening factors and physical environment. The research results show that there are 30 problems in listening to daily situational topics. They have 7 problems in the listening material, 14 problems in the audience factor, and 9 problems in the physical environment.